The Use of ICT in Prosumer Relations - Kocot, Maria (Wykorzystanie technologii ICT w relacjach prosumpcyjny, 2022)
The aim of the article is to analyse the use of ICT in prosumer relations. The hypothesis was formulated that these technologies play a huge role in the intensification of prosumption processes. A survey was conducted on a group of 500 respondents from the Śląskie voivodeship. The conducted research clearly showed that ICT plays a significant role in strengthening prosumption relations. By using them, prosumers can express their opinions, add comments, and contact manufacturers, providing them with tips so that they can improve their products, and ask questions about the products they use or plan to use. By using telecommunications and IT devices, they can also take part in actions organised by enterprises, and thus become co-creators of the product offer and its attributes. It was also emphasised that the Internet remains the most common ICT tool.
Informatyka Ekonomiczna = Business Informatics, 2022, Nr 1 (63), s. 20-28
Keywords: ICT; prosumers; internet; enterprise; consumers; technologie ICT; prosumenci; przedsiębiorstwo; konsumenci